Exploited Fishery Resources of Muvattupuzha River, Kerala, India - Renjithkumar, C. R.; Roshni, K.; Kurup, B. Madhusoodana (Fishery Technology, 2025)
The exploited fishery resources of Muvattupuzhariver have been estimated as 45.01 t during 2009-10.Twenty three fish species belonging to 6 orders and20 genera contributed to the fishery of this river.Highest landings was recorded during post-monsoonseason (21.87 t) followed by pre-monsoonseason (15.77 t) and lowest in monsoon (7.38 t).Family Cyprinidae ranked first among fish groupswith a numerical strength of 6 species. The landingswere represented by two endangered (Hypselobarbuscurmuca and Tor khudree) and one vulnerable(Horabagrus brachysoma) fish species. Gibelion catlawas the only non-native species represented in thelandings and Clarias gariepinus were the non-nativespecies represented in the landings. Wallago attu(7.62 t), Labeo dussumieri (7.21 t), H. curmuca (4.90 t),Channa striatus (4.6 t) and H. brachysoma (3.67 t) werethe dominant fishes in the landings. Among thelanding centres, Mulakulam accounted for 32% tothe total fish landings, followed by Kalampoor(27%). Gillnets (88%) contributed the major bulk ofthe fish landings followed by seine nets (11%). Catchper unit effort recorded in gillnet for major specieswere W. attu (0.11 kg h-1), Channa striata (0.08 kg h-1), T. khudree (0.08 kg h-1), G. catla (0.08 kg h-1) andC. marulius (0.07 kg h-1). In seines, highest catch perunit effort was recorded for C. striata (0.28 kg h-1)followed by C. marulius (0.20 kg h-1) and H.brachysoma (0.08 kg h-1).